Myself when I am real : the life and music of Charles Mingus - Santoro, Gene (OUP E-Books., 2001)
A pioneering bassist and composer, Mingus redefined jazz's terrain. He penned over 300 works spanning gutbucket gospel, Colombian cumbias, orchestral tone poems and chamber jazz, but got attention less for his art than his volatile behaviour. This biography offers a portrait of the musician.